Parathyroid hormone/parathyroid hormone-related protein receptor signaling is required for maintenance of the growth plate in postnatal life - Hirai, Takao (National Academy of Sciences, 2011)
Parathyroid hormone (PTH)-related protein (PTHrP), regulated by Indian hedgehog and acting through the PTH/PTHrP receptor (PPR), is crucial for normal cartilage development. These observations suggest a possible role of PPR signaling in the postnatal growth plate; however, the role of PPR signaling in postnatal chondrocytes is unknown. In this study, we have generated tamoxifen-inducible and cartilage-specific PPR KO mice to evaluate the physiological role of PPR signaling in postnatal chondrocytes. We found that inactivation of the PPR in chondrocytes postnatally leads to accelerated differentiation of chondrocytes, followed by disappearance of the growth plate. We also observed an increase of TUNEL-positive cells and activities of caspase-3 and caspase-9 in the growth plate, along with a decrease in phosphorylation of Bad at Ser155 in postnatal PPR KO mice. Administration of a low-phosphate diet, which prevents apoptosis of chondrocytes, prevented the disappearance of the growth plate. Taken together, these observations suggest that the major consequences of PPR activation are similar in both the fetal and postnatal growth plates. Moreover, chondrocyte apoptosis through the activation of a mitochondrial pathway may be involved in the process of premature disappearance of the growth plate by postnatal inactivation of the PPR in chondrocytes.